Актові книги як джерело з історії України ранньомодерної доби - Висотін, Микола (Київський національний університет імені Тараса Шевченка, 2024)
Подано узагальнюючу інформацію щодо сутності актових книг як історично го феномену. Схарактеризовано особливості функціонування українських судово-адміністра тивних органів України XVI–XVII ст., продуктом діяльності яких є актові книги. Висвітлено властивості системи ведення актових книг, головні підходи до класифікації та їх особливос ті як джерела для наукових досліджень.

Relevance of the research. Act books of the judicial and administrative bodies of Ukraine, particularly the grodskyi (city) and zemstvo courts, are an important historical source in the history of Ukraine in the early modern era. They contain significant information in terms of volume and value on various aspects of the historical process: the state of economic development of contemporary society, the judicial system, social history, private life, etc. The purpose of the study is to generalize and update the material concerning the essence of act books as a valuable source and historical phenomenon, set out in separate investigations and works devoted to the activities of Ukrainian judicial and administrative bodies of the 16th–17th centuries (grodskyi and zemstvo courts), as well as organizations established in the 19th century for the collection, storage, study and publication of historical documents (including act books) – the Temporary Commission for the Analysis of Ancient Acts under the Kyiv, Volyn and Podolsk Governor-General (better known as the Kyiv Archeographic Commission) and the Kyiv Central Archive of Ancient Acts. Conclusions. Act books were and remain a valuable historical source up to this day. They are of interest to Ukrainian scholars and foreign researchers, primarily those countries that were once part of the multinational state of the Polish-Lithuanian Commonwealth (Poland, Lithuania, Belarus). It is possible to solve a number of scientific problems that are key to Ukrainian cultural and historical identity based on a solid source base, which act books constitute. Today, this task is strategic. The new knowledge about the historical past of the Ukrainian people obtained based on the study of act books should be used for the transformation of modern historical education, as well as in all links of the educational process within the concept of continuity of education. the popularization of scientifically reliable and balanced knowledge about little-studied or falsified aspects of the history of Ukraine can be used in the system of measures for national patriotic education.
Act Books as a Source of the History of Ukraine in the Early Modern Era
Keywords: актова книга; ґродський суд; земський суд; возний; староста; підстароста; писар; суддя; Україна; Волинь; класифікація; історичне джерело; act book; grodskyi court; zemstvo court; voznyi; starosta; pidstarosta; scribe; judge; Ukraine; Volyn; classification; historical source